In situ observation of the evolution of porous silicon interference filter characteristics. - Volk, J.; Ferencz, K.; Ramsden, Jeremy J.; Tóth, A. L.; Bársony, I. (Wiley-VCH Verlag GmbH & Co. KGaA, 2005)
Porous silicon multilayer formation was observed by in situ monitoring of the reflectivity spectra in the visible range. In order to reproduce the formation process optical model simulation was carried out. For demonstration of this method a 24-layer microcavity structure was selected. Although in this low wavelengths region some absorption and scattering effects complicate the overall picture, the combined analysis throws new light upon the evolution of the porous silicon multilayer.